Low-latitude expressions of high-latitude forcing during Heinrich Stadial 1 and the Younger Dryas in northern South America - Bahr, André (Global and planetary change, 2018)
Changes in Atlantic Meridional Overturning Circulation (AMOC) strength exert a major influence on global atmospheric circulation patterns. However, the pacing and mechanisms of low-latitude responses to high-latitude forcing are insufficiently constrained so far. To elucidate the interaction of atmospheric and oceanic forcing in tropical South America during periods of major AMOC reductions (Heinrich Stadial 1 and the Younger Dryas) we generated a high-resolution foraminiferal multi-proxy record from off the Orinoco River based on Ba/Ca and Mg/Ca ratios, as well as stable isotope measurements. The data clearly indicate a three-phased structure of HS1 based on the reconfiguration of ocean currents in the tropical Atlantic Ocean. The initial phase (HS1a) is characterized by a diminished North Brazil Current, a southward displacement of the ITCZ, and moist conditions dominating northeastern Brazil. During subsequent HS1b, the NBC was even more diminished or yet reversed and the ITCZ shifted to its southernmost position. Hence, dryer conditions prevailed in northern South America, while eastern Brazil experienced maximally wet conditions. During the final stage, HS1c, conditions are similar to HS1a. The YD represents a smaller amplitude version of HS1 with a southward-shifted ITCZ. Our findings imply that the low-latitude continental climate response to high-latitude forcing is mediated by reconfigurations of surface ocean currents in low latitudes. Our new records demonstrate the extreme sensitivity of the terrestrial realm in tropical South America to abrupt perturbations in oceanic circulation during periods of unstable climate conditions.
Available online 10 November 2017
Gesehen am 03.03.2020